Dispute for the higher intercultural education in conflict scenes. Guerrero case, Mexico - Vargas Moreno, Paola (2020)
Mexico possess a system of Intercultural Universities built “from the top” (of the government) that after ten years of implementation presents important limitations derived from the hegemonic state indigenism. As an alternative, education experiences have emerged  “ from below” ( from the indigenism people) to build a counterhegemonic and autonomous  higher education , closer to the local necessities, however financing and legality of these process put them in a juncture that mark their relations (conflict- business) with the government. This dispute scenario becomes even more complex when the territories where this projects take place are conflict scenarios between the government, political parties, local guerrillas, drug trafficking and different forms of the own local community justice, as it is in the Guerrero area in Mexico.  In this context, this document: I) show us the way the dispute has been increase in relation to the reason and the duty of the Intercultural Higher Education, in Guerrero.  II) It places as a variable, the relation of the experiences with the local violence context and, III) it shows the lack of dichotomy “from the top” vs, “from below”, all of this considering the creation and development of two local intercultural universities.